Antibacterial activity of intermetallic NixMgy and NiO–MgO phases in nickel-magnesium oxide nanocomposites. (January 2023) - Ouafek, N.; Keghouche, N.; Beaunier, P.; Belloni, J.; Mostafavi, M.
Abstract: This work focuses on Ni–Mg metallic nanomaterials and NiO–MgO composites, especially on their antibacterial activity against Escherichia coli ( E. coli (G-) ) and Staphylococcus aureus ( S. aureus (G+) ) in relation with their size and structure. They are generated by impregnation of nickel formate, followed by either calcination (T = 100–600 °C) or gamma-irradiation at room temperature. In samples prepared by calcination at temperatures T ≤ 300 °C or irradiation, the structural study by XRD and HRTEM reveals the presence of nanoscaled Ni–Mg intermetallic phases: NiMg2, Ni2 Mg and NiMg6.33 (2–4 nm diameter) and magnesium hydroxide Mg(OH)2 . At T > 300 °C, only the NiO–MgO solid solution is formed. Bare MgO and NiO–MgO nanoparticles exhibit a bacterial activity only against E. coli and S. aureus, respectively. In contrast, the Ni–Mg intermetallic phases of high specific area, that are present in irradiated (T = 20 °C) or calcined (T ≤ 300 °C) samples, exhibit a significant antibacterial activity against both E. coli and S. aureus . Highlights: Irradiation (20 °C) or calcination of Ni 2+ /MgO give rise to intermetallic Nix Mgy . Ni 2+ ions are reduced into Ni clusters in presence of formate under basic conditions. Ni/MgO samples calcined at T = 300 °C display a large specific area (93.3 m 2 g −1 ). The toxicity against S. aureus and E . coli is due to a synergistic effect of Ni and Mg.